Humans and their technologies play the infinite game - Jouhki, Jukka (Human Technology, 2019)
Technology is increasingly about intuitive use and automation, as is evident to some degree in all the papers published in this issue. Technological--and one could say, even civilizational--progress is made possible by automating necessary but often tedious and tiresome processes. This then frees people's time and energy for a variety of recreational, inspirational, and/or developmental tasks. However, as the automation of society advances, the meaning of work changes and new existential and ethical questions emerge.